Investigating e-WOM via TikTok Impact on Purchase Intention: Brand “S” - Arie Setiawan; Teresa Gabriella; Wulan Darmawan; Yuli Rakasiwi (Dinasti Research, 2024)
This journal investigates the impact of social media marketing, particularly on TikTok, on the purchase intention of skincare products among Indonesian young adults, with a focus on the case study of skincare brand